IDENTIFIKASI POTENSI BAHAYA KERJA DAN PENGENDALIAN DAMPAK DI UNIT PRODUKSI PALM KERNEL CRUSHING PT. WILMAR CAHAYA INDONESIA PONTIANAK TAHUN 2014 - ., Indah Safitri (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background:Industrialization is the central to economic development andimproved prospects for human well-being. Industrial workers are at higherrisk of health conditions. Occupational hazards includes chemical hazards,physical hazards, biological hazards, ergonomic hazards, and psychology hazards. Hazards identification is needed to minimize the potential safety and health among industrial workers.Objective: To determine thepotential occupational hazards and control of impact on palm kernelcrushing at PT. Wilmar Cahaya Indonesia 2014.Methods: This studyused a qualitative study to explore more about potential occupationalhazards at PT. Wilmar Cahaya Indonesia 2014. The sampling techniquesthat was used in this study was purposive sampling and data wereanalyzed using triangulation method.Results: The chemical hazards arecaustic soda chemicals, exposure to dust, and fume. Physical hazards arenoise, vibration, poor lighting, heat temperature, and radiation. Biologicalhazards includes clean water area, latrine and landfills. Ergonomichazards include non-ergonomic working position. Psychological hazardsare night work hours and workload. Control of impact is done to controloccupational hazards. Controlling the impact using administrative aretraining, safety sign, and housekeeping. Controlling the impact is doneusing personal protective equipment such as ear plug, safety helmet,safety shoes, gloves, welding gloves, welding mask, safety googles, andmask. Conclusions: Potential hazards on palm kernel crushing PT.Wilmar Cahaya Indonesia are chemical hazards, physical hazards,biological hazards, ergonomics hazards, and psycology hazards. Controlling the impact that has been done by PT. Wilmar Cahaya Indonesia are administrative control and the use of personal protectiveequipment.Keywords: Identification of potential occupational hazards, control of impact.1. Medical School, Faculty of Medicine, Tanjungpura University, West Kalimantan. 2. Department of Community Medicine, Faculty of Medicine, Tanjungpura University, West Kalimantan.3. Department of Community Medicine, Faculty of Medicine, Tanjungpura University, West Kalimantan.